What is the solution of the equation (x – 5)2 + 3(x – 5) + 9 = 0? Use u substitution and the quadratic formula to solve.

Here is the answer for the question – What is the solution of the equation (x – 5)2 + 3(x – 5) + 9 = 0? Use u substitution and the quadratic formula to solve.. You’ll find the correct answer below

What is the solution of the equation (x – 5)2 + 3(x – 5) + 9 = 0? Use u substitution and the quadratic formula to solve.

The Correct Answer is

x = -3±3i√3/2_x = 7±3i√3/2x = 2x = 8

Reason Explained

x = -3±3i√3/2_x = 7±3i√3/2x = 2x = 8 is correct for What is the solution of the equation (x – 5)2 + 3(x – 5) + 9 = 0? Use u substitution and the quadratic formula to solve.

Thankyou for using answerout. We hope you get all your answers here. If you have any special questions, you can comment to ask us.

See also  Which action cannot be performed through a successful SQL injection attack?

Leave a Comment